Analisis Kinerja Keuangan Perusahaan dalam Perspektif Ekonomi Islam Melalui Pengungkapan Corporate Social Responsibility (CSR) - Mayndarto, Eko Cahyo (ITB AAS INDONESIA Surakarta, 2022)
CSR (Corporate Social Responsibility) is a form of commitment and action to fulfill the responsibility towards the surrounding social community and the environment by the company. This study aims to determine the effect of CSR disclosure on company performance in the Islamic Economic Perspective. This type of research is quantitative and associative with panel data method. Sources of data used are secondary data in the form of company annual reports and company financial statements published by the Indonesia Stock Exchange and the company's website. The data collected is processed using SPSS 16. Based on the results of data processing, the results of CSR Disclosures have an effect on the Company's Financial Performance in the Islamic Economic Perspective. Companies in Islam are responsible for paying attention to the community and the surrounding environment. Companies in Islam are required to be active in paying attention to the environment as a form of love for the universe, this makes it clear how important the relationship between Islamic economics and the natural environment and society is.